2016
DOI: 10.5670/oceanog.2016.32
|View full text |Cite
|
Sign up to set email alerts
|

Biological Impacts of the 2013–2015 Warm-Water Anomaly in the Northeast Pacific: Winners, Losers, and the Future

Abstract: A large patch of anomalously warm water (nicknamed "the Blob") appeared off the coast of Alaska in the winter of 2013-2014 and subsequently stretched south to Baja California. This northeastern Pacific warm-water anomaly persisted through the end of 2015. Scientists and the public alike noted widespread changes in the biological structure and composition of both openocean and coastal ecosystems. Changes included geographical shifts of species such as tropical copepods, pelagic red crabs, and tuna; closures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
473
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 558 publications
(500 citation statements)
references
References 49 publications
14
473
0
13
Order By: Relevance
“…To provide greater context on the influence of ocean climate conditions on biodiversity, we compare and contrast 3 extreme climate episodes: the 1997 El Niño, the 1999 La Niña and the 2015 warm blob. The ocean climate conditions during 1997 and 1999 represent extreme warm and cool years, while 2015 was unprecedented and impacted multiple aspects of the marine food web of the North Pacific (Bond et al 2015, Leising et al 2015, Cavole et al 2016, DiLorenzo & Mantua 2016. We calculated anomalies for satellite remotely sensed SST for the California Current and CTD cross-sections of temperature vertical structure to examine ocean conditions during May coinciding with biodiversity spatial anomalies during these years.…”
Section: Ocean Climate Conditions and Biodiversity Anomaliesmentioning
confidence: 99%
“…To provide greater context on the influence of ocean climate conditions on biodiversity, we compare and contrast 3 extreme climate episodes: the 1997 El Niño, the 1999 La Niña and the 2015 warm blob. The ocean climate conditions during 1997 and 1999 represent extreme warm and cool years, while 2015 was unprecedented and impacted multiple aspects of the marine food web of the North Pacific (Bond et al 2015, Leising et al 2015, Cavole et al 2016, DiLorenzo & Mantua 2016. We calculated anomalies for satellite remotely sensed SST for the California Current and CTD cross-sections of temperature vertical structure to examine ocean conditions during May coinciding with biodiversity spatial anomalies during these years.…”
Section: Ocean Climate Conditions and Biodiversity Anomaliesmentioning
confidence: 99%
“…The damage caused by MHWs is not only confined to demersal organisms or coastal ecosystems, e.g., a MHW in the North West Atlantic Ocean in 2012 indicated that these kinds of extreme events are also able to impact multiple commercial fisheries (Mills et al, 2013). When extreme enough, such as "The Blob" that persisted in the North West Pacific Ocean from 2014 to 2016, a MHW may negatively impact even marine mammals and seabirds (Cavole et al, 2016). Besides increases in mortality due to thermal stress, MHWs may also lead to outbreaks of disease in commercially viable species, such as that which occurred during the 2015/16 Tasman Sea event (Oliver et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Recent record high sea surface temperature anomalies (SSTa) in the California Current Large Marine Ecosystem (CCLME; Fig. 6.1a) produced dramatic impacts on marine life (Cavole et al 2016;Peterson et al 2016;Welch 2016). While effects on many species and fisheries may have been short-lived, salmon fisheries, for example, were heavily impacted in 2016 due to multiyear persistence of unfavorable conditions.…”
mentioning
confidence: 99%
“…These shifts in the prey base and predator distributions favor reduced growth and survival rates for CCLME salmon (e.g., Daly et al 2017), and anomalously warm CCLME SSTs are associated with low post-release survival rates for hatchery-origin coho and Chinook salmon from southeast Alaska to California (Sharma et al 2012;Kilduff et al 2015). While links between salmon abundance (or catch) and SST are not easily evaluated with time series correlations (see online supplement material), a strong link between record-warm 2014-16 CCLME SSTs and negative impacts on the West Coast salmon fishery in 2016 is evidenced by a shift to subtropical species and widespread negative impacts (increased mortality rates, reduced reproductive success and/or abundance) on top predators like sea birds, salmon, and marine mammals that typically thrive under neutral or cool SST conditions (Cavole et al 2016;Peterson et al 2016;Welch 2016). Anthropogenic forcing contributions to extreme warming were assessed using SSTa distributions from "historical" (1920-50) and "present" (2000-30) periods in the Coupled Model Intercomparison Project Phase 5 (CMIP5; Taylor et al 2012) ensemble and the Community Earth System Model Large Ensemble Project (CESM-LENS; Kay et al 2015).…”
mentioning
confidence: 99%